2017
DOI: 10.1155/2017/9549284
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Menstrual Cycle on Perioperative Bleeding in Vitreoretinal Surgery

Abstract: Purpose. To investigate the effect of menstrual cycle on perioperative bleeding of primary vitreoretinal surgery. Methods. Data on female patients who had vitrectomy surgery was retrospectively collected. Exclusion criteria were history of trauma, vitreous hemorrhage, previous vitreoretinal surgery, diabetic retinopathy, endophthalmitis, acute retinal necrosis, single vitreous opacity, and use of antiplatelet agents. Perioperative bleeding was defined as hemorrhage in the iris, vitreous, choroidal, retina, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A study by Lin et al . 22 found that menstruation had no significant effect on operative bleeding in vitreoretinal surgery. It was found by Das et al .…”
Section: Discussionmentioning
confidence: 93%
“…A study by Lin et al . 22 found that menstruation had no significant effect on operative bleeding in vitreoretinal surgery. It was found by Das et al .…”
Section: Discussionmentioning
confidence: 93%
“…However, some studies have shown contradictory results. A study by Lin et al (21) found that menstruation had no signi cant effect on operative bleeding in vitreoretinal surgery. It was found by Das et al that women undergoing open heart surgery during menstruation did not experience an increase in both surgical and menstrual blood loss (22).…”
Section: Discussionmentioning
confidence: 98%
“…Zhong Lin et al [ 24 ] examined blood loss in patients undergoing vitreoretinal surgery during the perimenstrual phase (n = 69) and periovulatory phase (n = 86). They inferred that the phases of menstrual period do not in any way affect perioperative bleeding therefore, menstruation should not be a contraindication for vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 99%